Polarized corporate boards - Hoang, Thao; Ngo, Phong T.H.; Zhang, Le (Journal of Corporate Finance, 2025)
We show that political polarization among directors negatively affects corporate board effectiveness by reducing forced CEO turnover-performance sensitivity. Our results are more pronounced in presidential election years and for firms with more monitoring and advising needs. Polarization also increases the departure likelihood for directors who are ideologically distant from the rest of the board, making boards more politically homogeneous over time. Finally, we show that polarization in the boardroom lowers firms' investment- Q sensitivity and Environmental, Social and Governance (ESG) performance. Our findings highlight the real economic cost of political polarization.